Resurrection and re-description of Plethodontohyla laevis (Boettger, 1913) and transfer of Rhombophryne alluaudi (Mocquard, 1901) to the genus Plethodontohyla (Amphibia, Microhylidae, Cophylinae) - Adriana Bellati; Mark D. Scherz; Steven Megson; Sam Hyde Roberts; Franco Andreone; Gonçalo M. Rosa; Jean Noël; Jasmin E. Randrianirina; Mauro Fasola; Frank Glaw; Angelica Crottini (Zoosystematics and Evolution, 2018)
The systematics of the cophyline microhylid frog genera Plethodontohyla and Rhombophryne have long been intertwined, and their relationships have only recently started to become clear. While Rhombophryne has received a lot of recent taxonomic attention, Plethodontohyla has been largely neglected. Our study is a showcase of just how complex the taxonomic situation between these two genera is, and the care that must be taken to resolve taxonomic conundrums where old material, multiple genus transitions, and misattribution of new material obfuscate the picture. We assessed the identity of the historic names Dyscophus alluaudi (currently in the genus Rhombophryne), Phrynocara laeve and Plethodontohyla laevis tsianovohensis (both synonyms of Rhombophryne alluaudi) based on an integrative taxonomic approach harnessing genetics, external morphology, osteological data obtained via micro-Computed Tomography (micro-CT) and bioacoustics. We show that (1) the holotype of Dyscophus alluaudi is a member of the genus Plethodontohyla; (2) the Rhombophryne specimens from central Madagascar currently assigned to Rhombophryne alluaudi have no affinity with that species, and are instead an undescribed species; and (3) Phrynocara laeve and Dyscophus alluaudi are not synonymous, but represent closely related species, whereas Plethodontohyla laevis tsianovohensis is tentatively confirmed as synonym of D. alluaudi. We resurrect and re-describe Plethodontohyla laevis, and re-allocate and re-describe Plethodontohyla alluaudi on the basis of new and historic material.